Application of Tuned Vibration Absorbers in Fluid Mounts. (2009) - Mashayekhi, Mohammad Jalali; Vahdati, Nader
Abstract : The need to reduce the fuel consumption of vehicles leads to having lighter chassis' with lighter engines yet maintaining engine power. These new design requirements are in contrast with the vibration isolation requirements. To keep the vehicles light yet provide good cabin noise and vibration isolation, requires a new vibration isolation technology. Fluid mounts have been used in the aerospace and the automotive industry to provide cabin noise and vibration reduction for years. With the use of passive fluid mounts, the highest cabin noise and vibration reduction is achieved at a frequency called "Notch Frequency". But typical passive fluid mounts have only one notch frequency. So the best cabin noise and vibration reduction is only achievable at one frequency. In this paper, a new fluid mount design in combination with a tuned vibration absorber is proposed. Bond graph modelling technique is used to model the new fluid mount design. The physical model and simulation results are presented. The effect of the natural frequency of the TVA on the dynamic stiffness of the fluid mount is studied.